2018
DOI: 10.1186/s13256-018-1741-9
|View full text |Cite
|
Sign up to set email alerts
|

Marked attenuation of the amplitude of transcranial motor-evoked potentials after intravenous bolus administration of ketamine: a case report

Abstract: BackgroundIt is believed that ketamine does not affect motor-evoked potential amplitude, whereas various anesthetic drugs attenuate the amplitude of transcranial motor-evoked potential. However, we encountered a patient with marked attenuation of motor-evoked potential amplitude after intravenous bolus administration of ketamine.Case presentationA 15-year-old Japanese girl with a diagnosis of adolescent idiopathic scoliosis was admitted to our hospital to undergo posterior spinal fusion at T4–L3. After inducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
0
1
1
Order By: Relevance
“…Previous studies suggested that a low-dose bolus (0.5 mg/kg) with or without infusion (0.24 mg/kg/h) of ketamine does not suppress the amplitude of MEP 9,11. However, the present study and a recent case report12 confirm that bolus administration of ketamine (1 to 1.25 mg/kg) can reduce MEP amplitudes. Bolus administration of ketamine (4 mg/kg) has also been found to decrease the amplitude of MEP in a rabbit model 7.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…Previous studies suggested that a low-dose bolus (0.5 mg/kg) with or without infusion (0.24 mg/kg/h) of ketamine does not suppress the amplitude of MEP 9,11. However, the present study and a recent case report12 confirm that bolus administration of ketamine (1 to 1.25 mg/kg) can reduce MEP amplitudes. Bolus administration of ketamine (4 mg/kg) has also been found to decrease the amplitude of MEP in a rabbit model 7.…”
Section: Discussioncontrasting
confidence: 81%
“…However, a recent case report suggested that a bolus dose of ketamine (1.25 mg/kg) administered in an adolescent patient with idiopathic scoliosis significantly reduced MEP amplitude 12. Although a previous study concluded that ketamine (1 mg/kg) did not affect mean MEP amplitude, MEP was evoked by transcranial magnetic stimulation 13.…”
mentioning
confidence: 97%